Stocks Market Interdependence and Asian Financial Crisis: Empirical Evidence from Asean-Plus-Three - Abdul Rahim, R.; Sapian, R. Z.; Mohd Nor, A. H. S. (Universiti Sains Islam Malaysia, 2024)
This paper examines the impact of Asian financial crisis on stock market interdependence for the period of 16 years from January 1991 to December 2006 of ASEAN-plus-three stock markets. The preliminary results show that there is differential in risk-return behavior for pre-, during and post-crisis period. The adverse impact of the Asian financial crisis is clearly evident by the sharp decreases in average returns, coupled with sharp increases in return volatility. The results of the eight-market vector autoregressive analyses indicate that on a country-by-country basis, it is Thailand and Korea that apparently play the dominant role of influencing the stock market interdependence. This is rather surprising given the importance of Japan as one of the world's most advanced markets and the primary source of foreign funds for the other Asian markets. Overall, the results of this study lend strong evidence to support current' conception that an exogenous shock like the Asian financial crisis is capable of increasing the levels of stock market interdependence. More importantly, this study proves that such a change is only temporary. The implication of these findings on investors in the ASEAN-plus-three markets is that even though there are some losses in risk reduction benefits of international portfolio diversification due to increased integration, the impact is not permanent. Once the markets recover from the crisis and regain their tranquil conditions, the level of stock market interdependence drops to their pre-crisis level. As a result, these markets will once again become the primary choice for international portfolio investors.